2002
DOI: 10.1016/s0002-9149(02)02349-4
|View full text |Cite
|
Sign up to set email alerts
|

Predicting revascularization outcome in patients with coronary artery disease and left ventricular dysfunction (data from the SEMINATOR study)

Abstract: A main goal of revascularization in patients with chronic ischemic cardiomyopathy is to improve global left ventricular (LV) function. This study aimed to verify whether it is possible to predict an increase in LV ejection fraction (EF) after revascularization on the basis of the extent of LV asynergy, myocardial viability, and revascularization completeness. We studied 77 patients with chronic LV ischemic dysfunction using baseline resting and nitrateenhanced technetium-99m sestamibi single-photon emission co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Sciagra et al [2] found that the severity of baseline asynergy, the extent of myocardial viability, and completeness of revascularization are the main variables in predicting postoperative increases in LV ejection fraction. Using SPECT imaging, Morse et al [3] showed that survival is more favorable for surgically revascularized patients with ischemic LV dysfunction and myocardial viability, confirming the previous study by Pagley et al [4], which identified patients more likely to benefit from surgical revascularization based on 201 Tl scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…Sciagra et al [2] found that the severity of baseline asynergy, the extent of myocardial viability, and completeness of revascularization are the main variables in predicting postoperative increases in LV ejection fraction. Using SPECT imaging, Morse et al [3] showed that survival is more favorable for surgically revascularized patients with ischemic LV dysfunction and myocardial viability, confirming the previous study by Pagley et al [4], which identified patients more likely to benefit from surgical revascularization based on 201 Tl scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in prognosis is most likely due to relieving ischemia, thus preventing further injury to viable myocardium and some improvement in global left ventricular (LV) function. The extent to which LV function improves is dependent on the amount of viable myocardium 32–34 and the completeness of revascularization 35 . Revascularization should not be delayed in patients with viable myocardium as it is associated with a high mortality and lack of improvement in LV function 36…”
Section: Indication For Pci: Left Ventricular Dysfunctionmentioning
confidence: 99%
“…The extent to which LV function improves is dependent on the amount of viable myocardium [32][33][34] and the completeness of revascularization. 35 Revascularization should not be delayed in patients with viable myocardium as it is associated with a high mortality and lack of improvement in LV function. 36 Optimal revascularization in patients with impaired LV systolic function has not received proper attention and is in great need of review.…”
Section: Indication For Pci: Left Ventricular Dysfunctionmentioning
confidence: 99%